2021
DOI: 10.1371/journal.pcbi.1009318
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of a personalized neoantigen cancer vaccine and the human immune system

Abstract: Cancer vaccines are an important component of the cancer immunotherapy toolkit enhancing immune response to malignant cells by activating CD4+ and CD8+ T cells. Multiple successful clinical applications of cancer vaccines have shown good safety and efficacy. Despite the notable progress, significant challenges remain in obtaining consistent immune responses across heterogeneous patient populations, as well as various cancers. We present a mechanistic mathematical model describing key interactions of a personal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
(79 reference statements)
2
14
0
Order By: Relevance
“…After performing the Wilcoxon signed-rank test, we found that the highrisk group was negatively correlated with tumor-infiltrating immune cells, such as neutrophils, M1 macrophages, plasmacytoid dendritic cells, CD4 + T cells, and CD8 + T cells, whereas it was positively correlated with cancer-associated fibroblasts and M2 macrophages. Similarly, it has been reported that the abundance of infiltration of CD4 + T and CD8 + T cells plays an important role in immunotherapy by enhancing the immune response to tumor cells (Rodriguez Messan et al, 2021). Moreover, the high infiltration of M1 macrophages and the low infiltration of M2 macrophages predict satisfactory outcomes for tumor patients, because M1 macrophages have the ability to engulf cancer cells and M2 macrophages may inhibit inflammatory response and repair tissue (Al Haq et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…After performing the Wilcoxon signed-rank test, we found that the highrisk group was negatively correlated with tumor-infiltrating immune cells, such as neutrophils, M1 macrophages, plasmacytoid dendritic cells, CD4 + T cells, and CD8 + T cells, whereas it was positively correlated with cancer-associated fibroblasts and M2 macrophages. Similarly, it has been reported that the abundance of infiltration of CD4 + T and CD8 + T cells plays an important role in immunotherapy by enhancing the immune response to tumor cells (Rodriguez Messan et al, 2021). Moreover, the high infiltration of M1 macrophages and the low infiltration of M2 macrophages predict satisfactory outcomes for tumor patients, because M1 macrophages have the ability to engulf cancer cells and M2 macrophages may inhibit inflammatory response and repair tissue (Al Haq et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…We use our compartmental model published previously [ 33 ], which captures the interactions among the human immune system, tumor burden, and a personalized neoantigen peptide cancer vaccine. In this paper, we refer to this model as MRM.…”
Section: Methodsmentioning
confidence: 99%
“…The MRM model [ 33 ] was calibrated using patient-specific data from six patients with melanoma at different disease stages [ 34 ] to estimate key model parameters (see Table A and B in S1 Appendix for a summary of model parameters and estimated values). In our previous study [ 33 ], in silico experiments (virtual simulations) were performed to investigate the response of each patient to cancer immunotherapy and assess changes in tumor sizes, and global sensitivity analysis was performed to identify and study the behavior of parameters that majorly contribute to the uncertainty of outcomes of interest, such as immune response and tumor cell count.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations